PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT KUTA UTARA KABUPATEN BADUNG - Inasih Surya; I Wayan Sudemen; Nyoman Sumawidayani (Program Studi Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Warmadewa, 2024)
This research is a study on the influence of career development and work motivation on employee performance at the North Kuta Subdistrict Office, Badung Regency. This research aims to examine the extent of the influence of career development and work motivation on employee performance at the North Kuta Subdistrict Office, Badung Regency. This research is a causal associative study with a quantitative approach. The data collection techniques in this study include observation, questionnaires, and documentation methods. The respondents in this study consisted of 44 employees from the sub-district office using the saturated sampling method. The research results show that the influence of career development on employee performance has a regression coefficient value of 0.368, a t-value of 3.653, while the t-table value is 2.019 and the t-test significance value is 0.001 < 0.05. The influence of work motivation on employee performance has a regression coefficient value of 0.356, a t-value of 3.575, while the t-table value is 2.019 and the t-test significance value is 0.001 < 0.05. The influence of career development and work motivation on employee performance has an F-value of 38.225 with a significance of 0.000 < 0.05. The coefficient of determination value indicates that the influence of career development and work motivation on employee performance at the North Kuta District Office is 65.1%, while the remaining 34.9% is influenced by other factors not examined in this study.